Removal of sewage phosphorus by adsorption and mineral precipitation, with recovery as a fertilizing soil amendment - Jowett, Craig; Solntseva, Irina; Wu, Lingling; James, Chris; Glasauer, Susan (Water science and technology, 2018)
Clear sand adsorbs 15–35% total phosphorus (P) from septic tank effluent, but P is mobilized when low-P effluent is applied. Amorphous P compounds formed by alkali aluminate chemical addition may also be subject to leaching. Crystalline mineralization is the desired end effect that isolates P thoroughly from the water resource. Using new low-energy iron electrochemistry (EC-P process), dissolved ferrous iron reacts with sewage phosphate ions (PO4) and precipitates onto filtration medium as vivianite [Fe3(PO4)2·8H2O], as identified by scanning electron microscopy and X-ray diffraction and predicted from Eh–pH–aHPO42− phase relations. Removal rates of 90–99% in sand, soil and synthetic foam filters are obtained. The precipitation of vivianite demonstrates that P can be immobilized quickly and without intermediary adsorption phases, as with Fe-rich soils. Vitreous silicate material (VSM) or rockwool that traps and precipitates mineral P after EC-P treatment was investigated as a means of P reuse as a fertilizing soil amendment. Comparative soil leaching and growth studies using corn plants demonstrate that the VSM alone reduces P losses from soils, and that VSM which has received EC-P effluent is equivalent to or better than commercial superphosphate fertilizer.